Analysis and simulation of the spatiotemporal evolution pattern of tourism lands at the Natural World Heritage Site Jiuzhaigou, China. (September 2018) - Liu, Jun; Wang, Juan; Wang, Shenghong; Wang, Jingfan; Deng, Guiping
Abstract: This study researched the Natural World Heritage Site of Jiuzhaigou, China, which has a vulnerable ecological environment and booming tourism industry. Using satellite imaging with field calibration, we established the site's land-use databases for 2005 and 2015, analysed tourism land-use transformations, determined the driving mechanism behind land-use, and simulated the spatial patterns of tourism lands for 2025 and 2035. The results revealed that, during 2005–2015, the heritage site underwent dramatic land-use/land-cover change from tourism development. The tourism functions have been becoming more similar. Moreover, the distribution of tourism lands was determined by elevation and slope, as well as distances to transportation lands, watersheds, and existing lands. Between 2025 and 2035, the evolution of tourism lands is projected to gradually slow down, while the tourism functions of each village would still be dominated by accommodation and catering. Highlights: Tourism industry development caused dramatic LUCC in the Jiuzhaigou heritage site in 2005–2015. Accommodation and catering are dominant tourism functions in 2005–2015. Tourism lands distribution was determined by elevation, slope, and distances to main roads, watersheds, and existing lands. The activity degrees and transformation modes of tourism lands varied with each village. Based on our simulation, the evolution of tourism lands would gradually slow down in 2025–2035.